Tissue Factor Expression in Obese Type 2 Diabetic Subjects and Its Regulation by Antidiabetic Agents - Jing Wang; Theodore P. Ciaraldi; Fahumiya Samad (Journal of Obesity)
Objective. Increased coagulation activation may contribute to the high incidence of cardiovascular complications observed in obese and type 2 diabetes (T2D) subjects. Although tissue factor (TF), the primary initiator of coagulation is increased in obesity, its expression in adipose tissues and its association with metabolic parameters are unclear. We sought to compare TF expression in plasma and adipose tissues of obese subjects with and without T2D, its correlation with metabolic parameters, and regulation in response to antidiabetic drugs. Methods Subjects were recruited from diabetes clinics and adipose tissue was obtained by needle biopsy of lower subcutaneous abdominal depot. For the intervention study, subjects were randomized into treatment groups with rosiglitazone or metformin for 4 months. Results. Plasma TF antigen, activity, and adipose TF mRNA were greater in obese T2D subjects compared with obese nondiabetics. Plasma TF activity correlated with fasting insulin, glucose, and free fatty acids, (FFAs), and adipose TF mRNA correlated with plasma FFA. Plasma TF activity was reduced by metformin and increased with rosiglitazone treatment. Conclusions. Specific diabetes-related metabolic parameters, but not obesity per se, are correlated with TF expression. Regulation of TF activity by different classes of antidiabetic drugs may relate to protective or adverse cardiovascular outcomes.